An integrative typology of global strategy and global value chains: The management and organization of cross‐border activities. (8th July 2020) - Pananond, Pavida; Gereffi, Gary; Pedersen, Torben
Abstract: Research summary: We contend that a synthesis between the literatures on global strategy and global value chains (GVCs) is mutually beneficial. A typology of four themes—managed cross‐border activities, network optimization, bottom‐up upgrading, and strategic coevolution—illustrates the underlying concepts and mechanisms that these two approaches share in common. Our integrative typology provides an analytical framework to understand the interplay between the statics of GVC governance and the dynamics of firm strategy. Firm‐level actions are a key factor in effective GVC‐level policy making, and our framework provides a roadmap to analyze how major disruptions, such as digitalization and pandemics, affect the symbiotic relationships between GVCs and firm strategy. Managerial summary: While the global strategy literature has underplayed the interdependence among firms and other actors in global value chains (GVCs) and highlighted the scope for firm agency, the GVC literature limits the attention to firm strategies per se but puts more emphasis on the governance structure of global industries. In their strategic decision making, managers must take into consideration how firms are positioned along the value chain in terms of four themes: managed cross‐border activities; network optimization; bottom‐up upgrading; and strategic coevolution. Integrating the GVC view adds a further impetus to global strategy beyond the analysis of intra‐firm determinants. Conversely, integrating global strategy into GVC analysis entails a more dynamic view on behaviors of different actors in the value chain. Understanding these interactions enable managers and policy makers to better incorporate how changes and disruptions affect firm strategies within the governance of GVCs.